2011
DOI: 10.1159/000330343
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 Gene Polymorphisms Do Not Influence the Response to Treatment in Alzheimer’s Disease

Abstract: Background: Acetylcholinesterase inhibitors (AChEIs) are the treatment of choice for patients with Alzheimer’s disease (AD). However, their efficacy is moderate and differs from patient to patient. Recent studies suggest that the Q192R variant of the paraoxonase 1 gene (PON1) might affect individual susceptibility to these drugs. Methods: We investigated the influence of 3 single nucleotide polymorphisms (SNPs) in PON1 (rs 662, rs 854560, rs 705381) and the APOE common polymorphism in 101 Polish patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…97 Multiple studies have addressed the association between PON1 polymorphisms and AD. 91,[98][99][100][101][102][103][104][105] In a study with 756 AD subjects, the authors found no association between the two major PON1 polymorphisms and AD in African Americans or Caucasians. 91 The authors conclude that either these functional PON1 polymorphisms are not associated with AD, or that the relative risk is small.…”
Section: 70-73mentioning
confidence: 93%
“…97 Multiple studies have addressed the association between PON1 polymorphisms and AD. 91,[98][99][100][101][102][103][104][105] In a study with 756 AD subjects, the authors found no association between the two major PON1 polymorphisms and AD in African Americans or Caucasians. 91 The authors conclude that either these functional PON1 polymorphisms are not associated with AD, or that the relative risk is small.…”
Section: 70-73mentioning
confidence: 93%
“…Conversely, a study by Klimkowicz-Mrowiec found that neither the SNP on residue 192 nor the SNPs on residues 55 and 161 were associated with response to donepezil and rivastigmine in a Polish AD cohort (Klimkowicz-Mrowiec et al, 2011 ). Further studies are needed to elucidate whether PON-1 could be useful in predicting response to AChEI or not.…”
Section: Discussionmentioning
confidence: 95%
“…al. previously demonstrated that PON1 gene polymorphisms do not influence the response to treatment in AD [51]. So far, no study has investigated the relationship between responsiveness to the PON2 gene and cholinergic therapy.…”
Section: Discussionmentioning
confidence: 98%